Tarbiyyah (Nurturing character) of university students through co-curricular programs: the experience of Co-Curricular, Leadership and Virtues Center (CLAV), International Islamic University Malaysia (IIUM) - Abd. Rahman, Akmal Khuzairy (2016)
This paper intends to focus on the activities of Tarbiyah run by the Co-curricular, Leadership and Virtues Center at IIUM since its inception in 2003 until the present day. In this descriptive and analytical study, the program structure of the co-curricular activities will be presented in general and a special attention will be given to the aspects of Tarbiyah that are manifested in the various programs run by the center. The paper will also discuss about the challenges of running such programs and the mechanisms employed by IIUM to meet them through interviewing the present and past directors of the center. Feedbacks from students through surveys by the center and the tracer study will be analyzed and discussed to gain an insight on the effectiveness of the programs from the perspective of the students. Among the conclusions on the paper: Nurturing students character through Tarbiyah needs administrative support from the University management in the form of policy statement without which such implementation will be half-hearted or even impossible; content development for the modules, identifying capable trainers and instructors, students responses and perceptions are among the continuous issues and challenges that need continuous attention; the overall perception of the impact of programs is very positive as IIUM became also the benchmark for other local institutions for their Tarbiyah program.